Political Ecology of Land Function Change to Shallot Agricultural Land in Enrekang Regency - Putra N, Ichwnuttaqwa Dwi; Muhiddin, Amir (Journal of Contemporary Local Politics, 2022)
This article aims to determine the political ecology of land conversion into shallot farming land in Enrekang Regency with reference to political ecology indicators by Bryant and Bailey, namely: risks and benefits of actors (explaining the follow-up and benefits of the political ecology of land use change that occurs), impacts that arise (analysing the impacts that are caused), and relations between actors (analysing the relationship between each interest of the actors involved). This type of research uses a qualitative method that aims to provide a descriptive description of the political ecology of land conversion into shallot farming land in Enrekang Regency. Data sources consist of primary data obtained through interviews and secondary data taken from official documents, notes, reports, and archives that can be supported by the integrity of the primary data. The results of the study show that there are interests of the actors so that land conversion can occur; the impact arising from the expansion of shallot fields results in floods and landslides; and relations between expansion actors occur because there are no regulations or local rules that limit the conversion of land to land agriculture in Enrekang District.